2020
DOI: 10.1186/s13018-020-01783-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of platelet-rich plasma for plantar fasciopathy: a best-evidence synthesis

Abstract: Background Plantar fasciopathy (PF) is a very common disease, affecting about 1/10 people in their lifetime. Platelet-rich plasma (PRP) had been demonstrated to be useful in achieving helpful effects for plantar fasciopathy. The purpose of this study was to compare the pain and functional outcomes between PRP and corticosteroid (CS) or placebo for plantar fasciopathy through meta-analysis and provide the best evidence. Methods Litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…In patients who do not respond to first-line treatments and become chronic, various methods including CS injections, PRP injections, extracorporeal shock-wave therapy, or dry needling, may be considered. 2,4,9,10,13,14,[17][18][19][20][21][22][23][25][26][27][28]31,39 CS injections have become a popular second-line treatment method, with rapid improvement in pain scores in patients who do not respond to noninvasive conservative treatment methods. Although the efficacy of CS injection in the treatment of PF was previously thought to be due to the anti-inflammatory activity of CS; the prostaglandin-related anti-inflammatory effect of CS has become controversial after histopathologic studies revealed that PF is a degenerative condition and not an inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients who do not respond to first-line treatments and become chronic, various methods including CS injections, PRP injections, extracorporeal shock-wave therapy, or dry needling, may be considered. 2,4,9,10,13,14,[17][18][19][20][21][22][23][25][26][27][28]31,39 CS injections have become a popular second-line treatment method, with rapid improvement in pain scores in patients who do not respond to noninvasive conservative treatment methods. Although the efficacy of CS injection in the treatment of PF was previously thought to be due to the anti-inflammatory activity of CS; the prostaglandin-related anti-inflammatory effect of CS has become controversial after histopathologic studies revealed that PF is a degenerative condition and not an inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…In patients who do not benefit from first-line treatments and develop chronic PF, various methods including corticosteroid (CS) injections, platelet-rich plasma (PRP) injections, extracorporeal shock-wave therapy, and dry needling may be considered. 1,2,4,5,6,9,10,13,14,[17][18][19][20][21][22]23,[25][26][27][28]31,39 Previous studies suggest that PRP injection could help repair of degenerative plantar fascial tissue due to high growth factor, stimulation of angiogenesis, and the potential anabolic effect on collagen matrix degeneration. 2,9,12,15,23,25 The clinical improvement, including improvements in pain scores and functionality, seen after PRP injections has been thought to be longer lasting with PRP injections compared with CS injections, potentially because of this purported regeneration effect, and has become an alternative to CS injections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight reviews examined the efficacy of PRP over control or in comparison with other therapies for plantar fasciitis [37][38][39][40][41][42][43][44]. Four studies performed qualitative review without meta-analysis [37,39,43,44].…”
Section: Platelet-rich Plasma (Prp)mentioning
confidence: 99%
“…One study concluded PRP showed a significant decrease in VAS scores and two studies demonstrated improvement in AOFAS score at 12 months, but all studies showed no improvements over earlier intervals [40]. Yu et al evaluated 13 RCTs and conducted separate meta-analyses for PRP versus corticosteroid and PRP versus placebo [41]. While the authors concluded that PRP is not superior to corticosteroid, there was some evidence that PRP is better than placebo.…”
Section: Platelet-rich Plasma (Prp)mentioning
confidence: 99%